2003
DOI: 10.4049/jimmunol.170.4.1659
|View full text |Cite
|
Sign up to set email alerts
|

A Unique Population of Extrathymically Derived αβTCR+CD4−CD8− T Cells with Regulatory Functions Dominates the Mouse Female Genital Tract

Abstract: A better understanding of the regulatory role of genital tract T cells is much needed. In this study, we have analyzed the phenotype, distribution, and function of T lymphocytes in the female genital tract of naive, pregnant, or Chlamydia trachomatis-infected C57BL/6 mice. Unexpectedly, we found that the dominant lymphocyte population (70–90%) in the genital tract was that of CD3+αβTCRintCD4−CD8− T cells. Moreover, these cells were CD90low but negative for the classical T cell markers CD2 and CD5. The CD3+B220… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
53
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 36 publications
(28 reference statements)
7
53
1
Order By: Relevance
“…Others have reported that DN-Treg can down-regulate CD8 + T cell-mediated immune responses in autoimmune and infectious disease models [29,30]. Interestingly, DNTreg, derived from human peripheral blood, possess similar immune-regulatory functions as those we demonstrated [31].…”
Section: Introductionsupporting
confidence: 75%
“…Others have reported that DN-Treg can down-regulate CD8 + T cell-mediated immune responses in autoimmune and infectious disease models [29,30]. Interestingly, DNTreg, derived from human peripheral blood, possess similar immune-regulatory functions as those we demonstrated [31].…”
Section: Introductionsupporting
confidence: 75%
“…Although peripheral, competent § g T cell populations in normal mice usually contain almost exclusively SP CD4 + or CD8 + T cells, peripheral 'double negative' (DN) (CD4 -CD8 -) or DP (CD4 + CD8 + ) T cell subsets have been described in mice and man. DN § g T R cells that are derived from murine CD8 + T cells [21,22] can suppress alloresponses [23] or mucosal T cell responses [24]. Virus activation can induce a DP phenotype in human SP CD8 + T cells [25][26][27].…”
Section: Dp Cd4 + Cd8 > I + T Cellsmentioning
confidence: 99%
“…Immunoglobulin A (IgA) and IgG are found in uterine and vaginal secretions [80]. The normal healthy female genital tract harbours few T cells, but infection with Chlamydia trachomatis results in recruitment of CD4+ve and CD8+ve T cells [39]. The same study also found a unique population of T cells in the mouse uterus that appear to perform a regulatory role rather than a protective role.…”
Section: Adaptive Immunity In the Reproductive Tractmentioning
confidence: 91%
“…Hormones play a very important role in regulating host immunity in the genital tract, distinguishing this from other mucosal sites [39]. There is a vast body of literature on the influence of female hormones on cell populations, antigen presentation and cell function in the reproductive tracts of humans and mice (see [80] for review), but not in sheep.…”
Section: Female Reproductive Hormones and Innate Immunitymentioning
confidence: 99%
See 1 more Smart Citation